Cultural factors associated with healthful behaviors in India - Díaz, Héctor Luis (UANL, Facultad de Trabajo Social y Desarrollo Humano, 2005)
Policy makers, healthcare professionals and other human service providers have an ethical responsibility to provide effective services to different population subgroups. This ethical responsibility is also extended to the increasing number of Indian immigrants in the United States and other countries. The author proposes that knowledge of the clients’ ethnic identification is not enough to help human service providers provide culturally sensitive health and human services. This article identifies contextual as well as group based cultural factors that are likely to influence healthful behaviors. Such factors include: gender discrimination and the resulting inability of women to make decisions impacting their own health, tensions between Indian folk medicine and western medicine, social discrimination and the resulting inequitable access to health services by minority groups, culturally dictated forms of communication, the role of spirituality and religion, their culturally prescribed notion of time and attitudes towards time, group orientation and reliance on the family and friends during health crises. The article concludes with a discussion of the implications of specific Indian beliefs and behaviors for healthcare policy and service delivery.